Analisis Penerapan Standar Akuntansi Keuangan Entitas Mikro Kecil dan Menengah (SAK EMKM) pada UMKM - Ichwan, Ichwan (Sekolah Tinggi Ilmu Ekonomi GICI, 2025)
This study aims to determine the application of Mr. Suhali's MSME financial statements before using SAK EMKM and after using SAK EMKM. The rapid development of MSMEs in Indonesia, IAI has compiled financial accounting standards specifically for MSMEs, namely SAK EMKM. The existence of these standards makes it easy for MSME players to make accountable financial reports. However, there are still many MSME players who have not implemented SAK EMKM, one of which is Mr. Suhali. This research uses a qualitative descriptive approach. Primary data is data obtained from this research, using data collection techniques of observation, interviews, and documentation. This study obtained the results, namely the application of SAK EMKM to Mr. Suhali MSMEs by preparing financial reports on Mr. Suhali MSMEs. The financial statements include a statement of financial position, income statement, and notes to the financial statements